A Predator's Perspective of the Accuracy of Ant Mimicry in Spiders - Ximena J. Nelson (Psyche: A Journal of Entomology)
Among spiders, resemblance of ants (myrmecomorphy) usually involves the Batesian mimicry, in which the spider coopts the morphological and behavioural characteristics of ants to deceive ant-averse predators. Nevertheless, the degree of resemblance between mimics and ants varies considerably. I used Portia fimbriata, a jumping spider (Salticidae) with exceptional eyesight that specialises on preying on salticids, to test predator perception of the accuracy of ant mimicry. Portia fimbriata’s response to ants (Oecophylla smaragdina), accurate ant-like salticids (Synageles occidentalis), and inaccurate ant-like salticids (females of Myrmarachne bakeri and sexually dimorphic males of M. bakeri, which have enlarged chelicerae) was assessed. Portia fimbriata exhibited graded aversion in accordance with the accuracy of resemblance to ants (O. smaragdina > S. occidentalis > female M. bakeri > male M. bakeri). These results support the hypothesis that ant resemblance confers protection from visual predators, but to varying degrees depending on signal accuracy.